ชุดกิจกรรมการเรียนรู้ เรื่อง หลักปรัชญาของเศรษฐกิจพอเพียง กลุ่มสาระการเรียนรู้สังคมศึกษา ศาสนา และวัฒนธรรม โดยใช้ผังมโนทัศน์ เพื่อพัฒนาผลสัมฤทธิ์ทางการเรียน ของนักเรียนชั้นประถมศึกษาปีที่ 4 สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาสกลนคร เขต 3 - Singsena, Nipa; Sornphet, Supakorn; Kittikun, Ben; Norasarn, Anek; Siriseranee, Warothai (Journal of Graduate School Sakon Nakhon Rajabhat University, 2023)
The objectives of this research were: 1) to find the effectiveness of the learning activities packages of ‘The Philosophy of Sufficiency Economy’ in the social studies, religion, and culture department by using the conceptual diagram of Grade 4 students based on the standard criterion 80/80 2) to compare the learning achievement of the Grade 4 students between before and after learning by being the learning activities packages using the conceptual diagram. The sample group used for this study was Grade 4 students at Ban Dong Huai Piuey School, under Sakon Nakhon Primary Educational Service Area Office 3, totaling 19 students obtained by cluster random sampling. The statistics used for data analysis were mean, standard deviation and percentage. The research instruments consisted of 1) the learning activities packages of ‘The Philosophy of Sufficiency Economy’ 2) a learning achievement test The results of the study were as follows: 1) the learning activity packages of ‘The Philosophy of Sufficiency Economy’ in the social studies, religion, and culture course department by using the conceptual diagram had efficiency of 81.00/82.14, which was higher than the set criterion. 2) the Grade 4 students of Ban Dong Huai Piuey School had a higher learning achievement score after studying with the learning activities packages of ‘The Philosophy of Sufficiency Economy’ in the social studies, religion, and culture department by using the conceptual diagram than before studying with statistical significance of .01.